Investigating compensatory adjustments induced by rhythmic auditory stimulation for changes in temporal gait symmetry in lower-limb prosthetic users - Aliaa Gouda; Muhammad Zeeshan Arshad; Jan Andrysek (PLoS ONE, 2026)
Gait training is an important part of rehabilitation for prosthetic users, improving mobility and long-term health outcomes. This study investigated the effects of rhythmic auditory stimulation (RAS) on gait symmetry and overall movement patterns in lower-limb prosthesis users (LLPUs). We aimed to determine how RAS, designed to enhance temporal gait symmetry, influenced overall lower-limb kinematic patterns and whether such changes were beneficial or detrimental to gait. Analysis of discrete parameters and the Gait Profile Score (GPS) indicated that while RAS improved temporal symmetry, it did not significantly alter movement patterns for both transfemoral (TFA) and transtibial amputees (TTA). Subject-specific analyses revealed varied responses, with some LLPU participants showing improved gait symmetry without significant movement changes, while others exhibited compensatory adjustments. To further explore lower-limb kinematic changes associated with temporal symmetry, a perturbation-based task involving able-bodied (AB) individuals demonstrated the presence of unique kinematic changes, including reduced ankle plantarflexion and increased hip flexion, reflecting adjustments to synchronize with the asymmetric beat. Finally, subject-specific analyses revealed user experience as a key factor influencing the LLPU response. Participants with more years of prosthesis use demonstrated greater improvements in their overall gait pattern (GPS). This study highlights that RAS can improve gait symmetry in LLPUs without inducing other significant, compensatory changes in their movement patterns, a positive finding for clinical rehabilitation. However, our results show that individual responses can vary depending on factors such as prosthesis type and user experience and these should be considered in clinical care. Future research should explore a broader range of gait parameters and long-term effects of RAS to gain a comprehensive understanding of its impact on gait and rehabilitation.